Efficacy of R&D Work in Offshore Captive Centers: An Empirical Study of Task Characteristics, Coordination Mechanisms, and Performance - Mani, Deepa; Srikanth, Kannan; Bharadwaj, Anandhi (Information Systems Research, 2014)
Seizing the latest technological advances in distributed work, an increasing number of firms have set up offshore captive centers (CCs) in emerging economies to carry out sophisticated R&D work. We analyze survey data from 132 R&D CCs established by foreign multinational companies in India to understand how firms execute distributed innovative work. Specifically, we examine the performance outcomes of projects using different technology-enabled coordination strategies to manage their interdependencies across multiple locations. We find that modularization of work across locations is largely ineffective when the underlying tasks are less routinized, less analyzable, and less familiar to the CC. Coordination based on information sharing across locations is effective when the CC performs tasks that are less familiar to it. A key contribution of our work is the explication of the task contingencies under which coordination based on modularization versus information sharing yield differential performance outcomes.